1956
DOI: 10.1002/zaac.19562880304
|View full text |Cite
|
Sign up to set email alerts
|

Über die Konstitution der sauren Sulfite. V. Die Struktur des Disulfit‐(S2O‐)Ions und über den Reaktionsmechanismus der Disulfitbildung bei der Halbneutralisation der Schwefligen Säure

Abstract: Es wird für das Disulfit‐(S2O 52−‐)Ion aus dem Raman‐ und Ultrarotspektrum eine Konstitution gemäß der Formel und eine räumliche Struktur der Symmetrie C2v mit gewinkelter SOS‐Brücke abgeleitet. Daraus ergibt sich, daß die Bildung des S2O 52−‐Ions in wäßrigen, halbneutralisierten Schwefligsäurelösungen nur über die tautomere Hydroxylform des Hydrogensulfits (HOSO 2−) möglich ist, die als nur in geringsten Konzentrationen vorliegend, durch eine Isomerisationsumlagerung des stabilen HSO 3−‐Ions nachg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1959
1959
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…There appears to be no evidence of either H2SO3 or NH4OH. Figure 1, b, c, and d, provides no evidence of the existence of S2O5-2 in these solutions (24) and agrees with the early freezing point measurements of Foerster, Brosche, and Norberg-Schulze (8). If H2SO3, NH4OH, or S2O5-2 existed, there would presumably be a marked shift or change in absorption band such as occurs when 3 2 becomes NH4+ (Figure 1, e and h) or SO2• H2O becomes HSO3or SO3-2 (Figure 1, a to d, /, g).…”
Section: Infrared Absorption Spectrasupporting
confidence: 85%
See 1 more Smart Citation
“…There appears to be no evidence of either H2SO3 or NH4OH. Figure 1, b, c, and d, provides no evidence of the existence of S2O5-2 in these solutions (24) and agrees with the early freezing point measurements of Foerster, Brosche, and Norberg-Schulze (8). If H2SO3, NH4OH, or S2O5-2 existed, there would presumably be a marked shift or change in absorption band such as occurs when 3 2 becomes NH4+ (Figure 1, e and h) or SO2• H2O becomes HSO3or SO3-2 (Figure 1, a to d, /, g).…”
Section: Infrared Absorption Spectrasupporting
confidence: 85%
“…However, all the theoretical and practical work which has been done (3, 5, 6, 70, 71, 13, 25) on this system has been based on concentrations of species-i.e., HSOs~, NH4+, etc.-derived from vapor pressure measurements and equilibrium calculations assuming ideal solutions. Furthermore, previous workers have assumed that the solution contains the species H1", OH-, HSO3-, NH4+, H2SO3, solvated SO2, NH4OH, and solvated NH3, but recent experimental work has indicated that 2$03 (7) and NH4OH (7) do not exist and that S2O5-2 (24) might exist in these solutions. The added fact that anhydrous SO2 and NH3 react to form solids of varying compositions (4,28) suggests the formation of associated components.…”
mentioning
confidence: 99%
“…Dimerisation of hydrogen sulfite has been investigated in aqueous solution by conductometry, 32 as well as IR, 12,33 UV [6][7][8][9][10]34 and Raman 10,11,[35][36][37][38] spectroscopic techniques. Table 1 summarises the reported values for the dimerisation constant, K D , in the literature.…”
Section: And 4 and References Therein)mentioning
confidence: 99%
“…The S-S-0 (S03) angle is 100.5°, the S-S-0 (S02) angle is 98.5°, the O-S-O (S03) angle is 113°, and the O-S-O (S02) angle 106°( the S-S02 group is not coplanar). Sets of vibrational frequencies have been given by Simon (1956,214,216 Devarajan (1977), 216 and Meyer (1979,1980).160,213 Fifteen vibrational frequencies with no degeneracies are expected for this heptaatomic ion of low symmetry, and these have been provided in these sets (for the assignments see Devarajan216), with some uncertainties due to the presence of foreign ions (e.g., HS03") in the solutions studied. The set given by Meyer (1979)213 for a solution is representative: 168,200,235,309, 424, 510, 558, 587, 637, 655, 966, 1052, 1085, 1170, and 1196 cm"1, and leads to the value of Sx°(g) in Table VIII.…”
Section: F Ions Of the Type X2y" (N > 4)mentioning
confidence: 99%